2018
DOI: 10.3310/hta22320
|View full text |Cite
|
Sign up to set email alerts
|

The future for diagnostic tests of acute kidney injury in critical care: evidence synthesis, care pathway analysis and research prioritisation

Abstract: The National Institute for Health Research Health Technology Assessment programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 377 publications
1
78
1
Order By: Relevance
“…The initial search of economic databases identified a total of 2972 records, of which 2157 remained after deduplication. Eight titles 108,110,121,[129][130][131][132][133][134] were identified as potentially relevant based on their titles and/or abstracts. The full-text articles of these records were assessed for eligibility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search of economic databases identified a total of 2972 records, of which 2157 remained after deduplication. Eight titles 108,110,121,[129][130][131][132][133][134] were identified as potentially relevant based on their titles and/or abstracts. The full-text articles of these records were assessed for eligibility.…”
Section: Resultsmentioning
confidence: 99%
“…The full-text articles of these records were assessed for eligibility. Four studies 108,110,121,129,130 were found to meet the selection criteria and were included in the review. These studies were not subject to a formal assessment, but were used to assist in the overall development of the new analytical model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the potential of AKI in-vitro diagnostic tests to improve the management of patients with critical illness, Hall et al performed a systematic review associated with meta-analysis of sensitivity and specificity, cost-effectiveness evaluation, appraisal of analytical validity, care pathway analysis and value of information analysis. They searched various databases (including ClinicalTrials.gov, the Cochrane Library, Embase, Medline, PubMed and Web of Science) to identify relevant sources of information published after 2004 up to July 2015 3. Three tests (TIMP-2●IGFBP7, NGAL (neutrophil gelatinase-associated lipocalin) and cystatin C were subject to detail review.…”
Section: Methodsmentioning
confidence: 99%
“…VOI is an increasingly popular tool that can be used to generate information regarding the value of further investment into research, providing information that complements sensitivity analysis (15). Within the early modelling context, VOI can be used to identify key parameters in the model that are driving uncertainty around the expected cost-effectiveness outcomes, and thereby direct the focus and design of future research and development activities (16,17). VOI formed the basis of the recommendations of two projects outlined here (OPTIMA and AKI).…”
Section: Strengthsmentioning
confidence: 99%